Pengaruh Flash Sale, Gratis Ongkos Kirim dan Live Streaming terhadap Keputusan Pembelian (Studi pada Pengguna TikTokShop di Kabupaten Lamongan) - Solekhah, Afifatul Aprilia Yani; Sulton, Muhammad (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This research aims to analyze the influence of flash sales, free shipping and live streaming on purchasing decisions among TikTokShop users in Lamongan Regency. The type of research used is quantitative with an explanatory research method. This research was conducted in Lamongan Regency with a sample of 100 respondents from the entire population of TikTokShop users in Lamongan Regency. The sampling technique in this research is non-probability sampling with purposive sampling technique as the sampling technique. The data collection technique uses Google Form with a Likert scale. The data processing technique in this research uses SEM-PLS (Structural Equation Model Partial Least Square). The results of this research show that flash sales do not significantly influence decisions, but the free shipping and live streaming variables significantly influence purchasing decisions for TikTokShop users in Lamongan Regency.